DEVELOPMENT OF MODELING AND MAPPING OF GAMMA RADIATION DOSE AND HEAT IN RSG G.A. SIWABESSY - Rohanda, Anis
Reaktor Serba Guna G.A. Siwabessy (RSG-GAS) is the largest research reactor in Southeast Asia which plays a role as a national facility for irradiating material. One of the impacts, if the material is exposed to high-intensity gamma radiation, is the emergence of gamma heating. The penetration of gamma photons in various material configurations in the area around the reactor core also causes gamma radiation exposure received by radiation workers in the reactor building, which is expressed as a gamma dose. Gamma heating information is very important for analyzing the safety of reactor operation and the target material itself. Meanwhile the gamma dose data is used for the analysis of the safety of radiation workers related to working time management and radiation shield design along with other exposure analysis results. Therefore, it is necessary to develop modeling and gamma heating calculation software to produce calculation data that is close to the measurement data. So that under certain conditions (accidents) where measurements are not possible, the gamma heating data and gamma radiation dose can be represented from the calculation data. Modification and improvisation of the software carried out in this research is one of the novelties of this research. The intensity of gamma radiation which plays an essential role as a radiation source in calculating gamma dose and gamma heating, was estimated using the ORIGEN2 code. Gamma heating can be determined by measurements and calculations. Research on the gamma heating calculation in the irradiation target material in RSG-GAS has been initiated since the 1990s using the Gamset code. Until now, this program is still used when direct measurements with a calorimeter are difficult to apply. However, this program has limitations in the form of a calculation basis that is only limited to 3 energy groups (0.5 MeV; 1 MeV; 1.5 MeV), and calculation parameters are compiled for 35 MW power level. Therefore, in this study, a new program to estimate gamma heating based on the Gamset code was developed based on 18 gamma energy groups ranging from 0.01 MeV to 9.5 MeV mean energy level, which is named "NewGamset". The addition of the energy range base to 18 groups follows the energy spectrum of the ORIGEN2 code which is divided based on the energy and behavior of the reactor core inventory nuclides. NewGamset has implemented the adjustment of the RSG-GAS physical parameters for 15 MW as operational power and 30 MW as design power. In this study, gamma heating measurements were carried out in the Central Irradiation Position (CIP) of the RSG-GAS silicide core to verify the results of Gamset and NewGamset calculations. The measurement results at the operating power of 15 MW with four types of calorimeters, namely absorbent material of graphite (C), aluminum (Al), iron (Fe), and zirconium (Zr). The measurement results for each type of calorimeter are 2.20 W/g (C), 2.25 W/g (Al), 2.58 W/g (Fe) and 2.91 W/g (Zr). So that the calorimeter is chosen that produces the measurement results that are closest to the calculated data. In general, the calculation results are greater than the measurement results. The ratio of comparisons with Gamset code to measurement is 1.37, while with NewGamset is 1.02. Thus, it is concluded that NewGamset provides results that are closer to the measurement value when compared to the previous code (Gamset) so it is recommended to use it to validate gamma heating data for various irradiated target materials in RSG-GAS. NewGamset is also designed to be more user-friendly so that it is able to answer practical needs related to the safety analysis of irradiation facilities which is constrained by calorimeters repair problems and the implementation of measurement activities that can disrupt the schedule of material irradiation services in RSG-GAS. Radiation control activities at reactor facilities are carried out based on the ALARA (as low as reasonably achievable) principle to ensure safety for radiation workers, the community, and the environment. This activity is realized by measuring and calculating the gamma dose using an appropriate computer simulation program. In this study, the calculation and mapping of gamma doses were carried out in the Operation Hall (Lv.13) and the Experimental Hall (Lv. 0) as high-accessibility work areas using the QADCGGP code. This code is popularly used to calculate gamma photons' penetration in various media and for radiation shielding designs. Gamma sources are classified into 18 gamma energy groups according to the energy division in the NewGamset program to improve the accuracy of the calculation results. The results were verified by measurement using a gamma surveymeter (dosemeter) at a particular observation point radially in the RSG-GAS reactor building. In general, the gamma dose rate of the QADCGGP simulation results is lower than the measurement results. This is because the measurement area is taken as close to the area used as the calculation location, so that the calculation results are contaminated with radiation sources other than gamma radiation. The verification results showed an average difference: 4% ~ 7%. The mapping results are used for the zone classification, working time management, and as the basis for the radiation shields design in the working area. From the mapping results, most of the working area has low exposure category (L). Working areas with moderate (M) and high (H) exposure categories are found in the area around the core center, reactor pool, and beam tube S1, which are currently operating, and the areaaround the primary pump door.